Basal Cell Carcinoma: 10 Years of Experience. (7th November 2010) - Cigna, Emanuele; Tarallo, Mauro; Maruccia, Michele; Sorvillo, Valentina; Pollastrini, Alessia; Scuderi, Nicolò
Abstract : Introduction . Basal cell carcinoma (BCC) is a locally invasive malignant epidermal tumour. Incidence is increasing by 10% per year; incidence of metastases is minimal, but relapses are frequent (40%–50%). The complete excision of the BCC allows reduction of relapse. Materials and Methods . The study cohort consists of 1123 patients underwent surgery for basal cell carcinoma between 1999 and 2009. Patient and tumor characteristics recorded are: age; gender; localization (head and neck, trunk, and upper and lower extremities), tumor size, excisional margins adopted, and relapses. Results . The study considered a group of 1123 patients affected by basal cell carcinoma. Relapses occurred in 30 cases (2, 67%), 27 out of 30 relapses occurred in noble areas, where peripheral margin was <3 mm. Incompletely excised basal cell carcinoma occurred in 21 patients (1, 87%) and were treated with an additional excision. Discussion . Although guidelines indicate 3 mm peripheral margin of excision in BCC <2 cm, in our experience, a margin of less than 5 mm results in a high risk of incomplete excisions.